House Staff Quality Council: One Institution's Experience to Integrate Resident Involvement in Patient Care Improvement Initiatives - Dixon, Jennifer L. (the Academic Division of Ochsner Clinic Foundation, 2013)
BACKGROUND: Residents and fellows perform a large portion of the hands-on patient care in tertiary referral centers. As frontline providers, they are well suited to identify quality and patient safety issues. As payment reform shifts hospitals to a fee-for-value–type system with reimbursement contingent on quality outcomes, preventive health, and patient satisfaction, house staff must be intimately involved in identifying and solving care delivery problems related to quality, outcomes, and patient safety. Many challenges exist in integrating house staff into the quality improvement infrastructure; these challenges may ideally be managed by the development of a house staff quality council (HSQC). METHODS: Residents and fellows at Scott & White Memorial Hospital interested in participating in a quality council submitted an application, curriculum vitae, and letter of support from their program director. Twelve residents and fellows were selected based on their prior quality improvement experience and/or their interest in quality and safety initiatives. RESULTS: In only 1 year, our HSQC, an Alliance of Independent Academic Medical Centers National Initiative III project, initiated 3 quality projects and began development of a fourth project. CONCLUSION: Academic medical centers should consider establishing HSQCs to align institutional quality goals with residency training and medical education.